Preparation of Arsenobetaine hydrobromide - Ismail, Hazar; Toia, Robert F. (1988)
Crystalline arsenobetaine hydrobromide is deposited directly on addition of trimethylarsine to a benzene solution of bromoacetic acid. The product is stable, non-deliquescent and may be readily converted into the free betaine by passage through basic ion exchange resin.